Meeting report: the 2022 British Adult Congenital Cardiac Nurses Association Annual Conference. (2nd April 2023) - Swift, Hannah; Habibi, Hajar; Anthony, James; Vernon, Sheena; Shaughnessy, Lynda; Griffiths, Linda; Lyon, Joy; Mercaldi, Rebecca; Simpson, Maggie
Abstract : In this month's BANCC column, Hannah Swift and colleagues provide an overview and brief discussion of last year's British Adult Congenital Cardiac Nurses Association Annual Conference.